Estimate the distribution parameters for the best rates of rainfall in Iraq - الوكيل علي عبد الحسين; هادي نبا صالح (Journal of Economics and Administrative Sciences, 2017)
This paper presents a statistical study for a suitable distribution of rainfall in the provinces of Iraq Using two types of distributions for the period (2005-2015). The researcher suggested log normal distribution, Mixed exponential distribution of each rovince were tested with the distributions to determine the optimal distribution of rainfall in Iraq. The distribution will be selected on the basis of minimum standards produced some goodness of fit tests, which are to determine Akaike (CAIC), Bayesian Akaike (BIC), Akaike (AIC). It has been applied to distributions to find the right distribution of the data of rainfall in the provinces of Iraq was used (maximum likelihood method, least squares method) to find the estimate of distribution parameters. Through the practical side it has been to reach a number of conclusions that the most important of the best probability distribution of rainfall data for most Iraqi provinces is either log normal distribution or mixed exponential distribution rate of ten provinces of the total twelve province distributed probability distribution is mixed exponential distribution.